Assessing the training needs of users in accessing electronic resources - Madge, Octavia-Luciana (Qualitative and Quantitative Methods in Libraries; Vol 4 No 4 (2015): December 2015 Issue, 2017)
One of the recent trends at the level of academic libraries has been the development of large electronic collections. Currently in many such institutions they almost reach the size of printed collections and many say that they will soon exceed them. In Romania, academic libraries have also started to give special attention to electronic documents and they provide at present access to a large range of electronic resources. However, research conducted by the author among the users of academic medical libraries in 2007, 2008 and 2011 revealed a low level of interest and usage of electronic information resources. An extended and more detailed investigation of these aspects was considered necessary and this paper presents the results of a 2013 research conducted among the users of two branches of the “Carol I” Central University Library of Bucharest, the Faculty of Political Sciences Library and the Faculty of Letters Library, and analyzes user behaviour in accessing library services and information resources.